'e-Grama': a tool for capacity building and bridging the digital divide in rural India. (14th February 2011) - Das, Rama Krushna; Patra, Manas Ranjan
This paper puts forth our experience while implementing the 'e-Grama' project in one of the relatively developed districts of Orissa Province in India which was later extended to other underdeveloped districts of the province. Further the paper describes how the project helped as a tool to bridge the digital divide and capacity building in the rural areas. It also highlights the role of youth clubs and NGOs in the successful implementation of the project. Further, it is shown how the problems encountered during project implementation in the rural areas could be solved through the public?private?people partnership model of 'e-Grama'.